KAJIAN PERTUMBUHAN DAN PRODUKSI KAMBING PERANAKAN ETTAWA JANTAN YANG DIBERI PAKAN BERBEDA - Suparman Suparman; Harapin Hafid; La Ode Baa (Universitas Halu Oleo, 2016)
This study aimed to analyze the growth and productivity of male bred Ettawa goats that are fed with different animal feeds. The study was conducted for 4 months, from January to April 2016, at the village of Ranomentaa in the sub district of Toari, Kolaka regency. The used involved 12 male bred Ettawa goats, aging between 4-6 months and placed in 12 individual cages. The study used the Complete Randomized Design with 3 treatments and 4 repetitions, including Treatment 1 (P1), P2 (50% of mulberry leaves, 50% of gliricidia leaves), and P3 (100% of gliricidia leaves). Parameters under observation in the study were increase of body weight (PBB), weight of slaughtered animal, weight and percentage of carcass, weight and percentage of non-carcass. Results of the study showed that the average of PBB of P3 (26.98 g/day) was significantly different (P<0.05) from P2 (22.83 g/day) and P1 (22.42 g/day), whereas P2 and P1 were not significantly different. This was in line with the average of slaughtered animal weight from the highest to the lowest, namely P3 (13.29 kg), P2 (11.21 kg), and P1 (10.37 kg), followed by the average of carcass weight which was significantly affected (P<0.05) by the treatment. The average of carcass weight was P1 (4.17 kg), P2 (4.42 kg), and P3 (5.38 kg), whereas the average of carcass percentage had no significant different (P<0.05) due to the treatment with the range of 38.43–39.43%. Similarly, the weight and percentage of non-carcass were within the range of 50.73–55.09%. Based on the results of this study, it could be concluded that while feeding goats with gliricidia and mulberry leaves had a significant effect on the increase of body weight, weight of slaughtered animal, and weight of carcass, it had no significant effect on carcass percentage, weight of non-carcass, and percentage of carcass.Keywords: gliricidia leaves, mulberry leaves, growth and productivity of male PE goats